IMPLEMENTASI METODE MOORA DALAM MENENTUKAN KELAYAKAN PENERIMA PROGRAM KELUARGA HARAPAN (PKH) - Rusdi Efendi; Aan Erlanshari; Miranti Nopita Sari (JSAI (Journal Scientific and Applied Informatics), 2022)
The Family Hope Program is a government program that provides conditional social assistance to very poor families that meet the requirements set by the Ministry of Social Affairs. Currently, in the Rimbo Pengadang sub-district, there is no system that can determine who is more eligible who has registered to receive the Hope Family Program. Thus, a decision support system to determine every citizen who registers. The purpose of this research is to build a decision support system in determining the recipients of the Family Hope Program using the MOORA method, then apply the MOORA method to be able to process the criteria in determining the eligibility of PKH recipients, generate value from MOORA . calculation method, dan menghasilkan peringkat untuk menentukan siapa yang memenuhi syarat untuk menerima Program Keluarga Harapan. The method used is the Multi-Objective Optimization by Ratio Analysis (MOORA) method. Tests in this study using Black-box testing get a value of 100%, testing the feasibility of the system with manual calculations obtained an accuracy value of 100%.